Effects of Salt Stress on Grain Quality and Starch Properties of High-Quality Rice Cultivars - Ruilong Cui; Tianyang Zhou; Chenchen Shu; Kuanyu Zhu; Miao Ye; Weiyang Zhang; Hao Zhang; Lijun Liu; Zhiqin Wang; Junfei Gu; Jianchang Yang (Agronomy, 2024)
In recent days, there has been a noticeable surge in demand for high-quality rice. However, the influences of salinity on the quality and starch properties of high-quality rice remain unclear. Three high-quality rice cultivars (Nanjing 9108, Nanjing 5055, and Nanjing 46) were studied to investigate the responses of grain quality to salt stress. There were three treatments, including a control zero salt level (0 g·kg−1, CK), and two salt levels of 0.1 g·kg−1 (0.1% salt stress, T1) and 0.2 g·kg−1 (0.2% salt stress, T2). The study involved the assessment of the appearance, milling, cooking, and eating qualities of rice. We also conducted an analysis of pasting properties, an evaluation of starch thermal properties, and an examination of the fine structure of amylopectin. The findings suggest that as the level of salt stress increases, the yield of rice gradually declines, which is primarily due to a significant reduction in the total spikelet number and the ratio of filled grains. Compared with CK treatment, the appearance and milling quality of rice were significantly improved within the T1 treatment. In addition, the protein concentration and amylose concentration were significantly decreased, the gel consistency was significantly increased, and the cooking and eating qualities were improved. In terms of starch properties, the peak viscosity, breakdown value, infrared ratio (1022/995), and short-chain-length amylopectin ratio increased significantly, while the setback value, pasting temperature, gelatinization enthalpy, relative crystallinity, and infrared ratio (1045/1022) decreased significantly. When comparing T2 with CK, the appearance quality and cooking and eating quality had deteriorated, and the milling quality was improved. The changes in the structural and physicochemical properties of starch were opposite to those in the comparison between the T1 treatment and the CK group. Accordingly, we propose that moderate salt stress has the potential to enhance rice quality, even though there may be a slight decrease in yield. This indicates that it is feasible to cultivate high-quality rice in saline–alkali beach areas.